Réponses

2014-05-16T17:52:35+02:00
(8+x)(100-2x) = 8*100+8*(-2x)+x*100+x*(-2x)
                      = 800-16x+100x-2x²
                      = -2x²+84x+800

(40-x)(20+4x) = 40*20+40*4x-x*20-x*4x
                       = 800+160x-20x-4x²
                       = -4x²+140x+800

(8+x)(100-2x) ≠ (40-x)(20+4x)
2014-05-16T18:07:33+02:00
(8+x)(100-2x)=(40-x)(20+4x)
800 - 16x + 100x - 2x2 = 800 + 160x - 20x - 4x2
-2x
² + 4x² - 16x + 100x - 160x + 20x = 0
2x
² - 56x = 0
Δ = b
² - 4ac
Δ = 56*56 - 0
Δ = 3136
Δ étant > 0 il y a deux solutions qui sont
x1 = (-b-√Δ)/2a et x2= (-b+√Δ)/2a
L'EQUATION A DEUX SOLUTION :
x1 = (-b-√Δ)/2a  ET  x2= (-b+√Δ)/2a
x1 = 0
x2 = 28